Penuntasan Wajib Belajar 12 Tahun di Provinsi DKI Jakarta - Muhamad Husin (Jurnal Pendidikan dan Kebudayaan, 2010)
Program nine years of compulsory education in Indonesia started launched in 1994 and finished in the year targeted 2008. However, in practice still have a lot of obstacles, among others, is the cost factor, the means of schooling, and the circumstances that require students to work, so that the target of completing the nine-year compulsory education as a whole have not been met. Special Province of DKI Jakarta program compulsory education of 9-year, has been successfully completed. Gross Enrollment Rate (GER) Junior High School for DKI Jakarta province in 2004 has reached 102.86%, while for senior high school by 81.41%. Based on these facts, it should provincial DKI Jakarta began improving education quality by improving citizens 12 years of mandatory programs. This is in accordance with the development of Jakarta as a city service that is parallel to the major cities the other in Asia, which requires human resources and strong excel in the service industry. In order for completing compulsory education reached 12 years, still required additional budget from the state budget, budget and community participation and the business world. Financing programs compulsory education to 12-year, should be directed to the management and supervision of financial resources and improving the quality of education.